Implementation of GRI and SDGs Achievements in MSMEs Sustainability Report - Noah Archer, Roy; Mardiana, Mardiana (Universitas Kristen Maranatha, 2025)
Purpose – This study aims to analyze how the implementation of the Global Reporting Initiative (GRI) and the achievement of Sustainable Development Goals (SDGs) by Micro, Small, and Medium Enterprises (MSMEs) affects their sustainability reporting, as well as to understand the factors underlying the success or challenges in applying these sustainability principles to MSMEs. Design/methodology/approach – This study uses a qualitative approach with a case study method. Data were collected through semi-structured interviews with owners or managers of MSMEs in Indonesia. A total of 12 MSMEs from various sectors on the island of Java were selected as research samples. Data analysis was conducted using a scoring method to identify and interpret the GRI and SDGs practices implemented by MSMEs Findings – The study results indicate that the level of GRI disclosure and SDGs implementation in MSMEs in Indonesia varies. Most MSMEs have an understanding of the importance of sustainability, but their implementation is still limited to basic aspects such as energy efficiency and waste management. The main challenges faced by MSMEs are limited resources, lack of understanding of reporting standards, and cost pressures. Research limitations/implications – This research has an impact on the development of theories regarding the implementation of GRI and the achievement of SDGs in the context of MSMEs. This study has limitations in the relatively small sample size and focus on MSMEs in Java, so the results may not be generalizable to all MSMEs in Indonesia. Future research can involve larger and more diverse samples Keywords: GRI, Sustainability Report, SDGs, MSMEs